Work meets life : exploring the integrative study of work in living systems - Levin, Robert (MIT Press, 2011)
The work performed by living systems ranges from photosynthesis to prodigious feats of computation and organization. This multidisciplinary volume explores the relationships between work and the study of work across many different levels of organization.